2019
DOI: 10.1155/2019/3276919
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Cocoon Syndrome: Two Cases of an Anatomical Abnormality

Abstract: Introduction. Idiopathic sclerosing encapsulating peritonitis or abdominal cocoon syndrome (ACS) is a rare anatomical deformity characterized by the partial or complete encasement of the small intestine with fibrotic peritoneum. 193 cases have been described worldwide. The aim of this study is to present two cases of ACS successfully treated at the Surgical Clinic of the Agios Dimitrios General Hospital in Thessaloniki, Greece. Presentation of Cases. Two men (55 and 54 years old) presented to the emergency dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Historically, SEP was considered to be more frequent in young girls living in tropical areas, which supported the theory of retrograde menstruation via the fallopian tube; however, recent reports including a systematic review showed that it is more frequent in males ( 12 , 13 ). In our review of the reported cases in the Arabian Gulf region, we found only eight cases of SEP, which are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 97%
“…Historically, SEP was considered to be more frequent in young girls living in tropical areas, which supported the theory of retrograde menstruation via the fallopian tube; however, recent reports including a systematic review showed that it is more frequent in males ( 12 , 13 ). In our review of the reported cases in the Arabian Gulf region, we found only eight cases of SEP, which are summarized in Table 2 .…”
Section: Discussionmentioning
confidence: 97%
“…Patients with mild symptoms may receive conservative treatment, such as nutritional support, gastrointestinal decompression, and medication. The renin-angiotensin-aldosterone system inhibitor therapy and anti-inflammatory agents, including colchicine and immunosuppressants (such as mycophenolate mofetil, azathioprine, cyclosporine, etc), have been found to be efficacious for the treatment of SEP. [ 17 ] In addition, corticosteroids and tamoxifen can also alleviate symptoms and restore bowel function in patients with SEP. [ 2 ] Hirahara et al successfully established a rat model of sclerosing peritonitis induced by the intraperitoneal injection of chlorhexidine gluconate and methylglyoxal, which can be used to analyze the mechanism of progression of peritoneal injury and EPS. [ 4 ] Ju et al applied this model, and reported that a novel AMP-activated protein kinase activator (HL156A) can reduce the degree of peritoneal fibrosis caused by chlorhexidine gluconate, suggesting that HL156A has clinical value in the treatment of SEP. [ 6 ] Surgery remains as the gold standard treatment for SEP. Surgical treatment is performed mainly through the release of the fibrous capsule and small intestinal adhesion, thereby relieving the intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically is characterised by an intermittent acute, sub-acute or chronic intestinal obstruction. In contrast, the acute form exhibits stronger symptomatology [4,20,21]. The involvement of the stomach, large intestine, liver or other abdominal organs are infrequently occurring [21].…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In contrast, the acute form exhibits stronger symptomatology [4,20,21]. The involvement of the stomach, large intestine, liver or other abdominal organs are infrequently occurring [21].…”
Section: Clinical Presentationmentioning
confidence: 99%